2010
DOI: 10.1016/j.envres.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Short-term association between sulfur dioxide and daily mortality: The Public Health and Air Pollution in Asia (PAPA) study

Abstract: Sulfur dioxide (SO2) has been associated with increased mortality and morbidity, but few studies were conducted in Asian countries. Previous studies suggest that SO2 may have adverse health effects independent of other pollutants. In the Public Health and Air Pollution in Asia (PAPA) project, the short-term associations between ambient sulfur dioxide (SO2) and daily mortality were examined in Bangkok, Thailand, and three Chinese cities: Hong Kong, Shanghai, and Wuhan. Poisson regression models incorporating na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(61 citation statements)
references
References 28 publications
2
57
1
1
Order By: Relevance
“…28 In addition, an intervention study in Hong Kong cutting down sulfur concentration in fuels has demonstrated direct health benefits after significant decrease in ambient SO 2 levels. 29 On the other hand, due to rapid increase in the number of motor vehicles, the MOEP is considering to add "total emission of NO 2 " as another index of air pollution control.…”
Section: Accountability Evaluation Of Air Pollution Control In Chinamentioning
confidence: 99%
“…28 In addition, an intervention study in Hong Kong cutting down sulfur concentration in fuels has demonstrated direct health benefits after significant decrease in ambient SO 2 levels. 29 On the other hand, due to rapid increase in the number of motor vehicles, the MOEP is considering to add "total emission of NO 2 " as another index of air pollution control.…”
Section: Accountability Evaluation Of Air Pollution Control In Chinamentioning
confidence: 99%
“…Several empirical studies highlight the association of nitrogen dioxide (NO 2 ), ozone (O 3 ), sulfur dioxide (SO 2 ) and carbon monoxide (CO) with adverse short-term effects, including increases in daily mortality, particularly cardiorespiratory mortality, and morbidity (Kan et al, 2010;Sousa et al, 2012;Zhang et al, 2013). NO 2 and O 3 have been observed to influence principally respiratory outcomes, while CO predominantly affects the cardiac system (Katsouyanni et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The longterm effect of exposure to low-concentration SO 2 is similar to the short-term effect of exposure to high-concentration SO 2 in many industrial settings and chemical industries. Numerous epidemiological studies have suggested that SO 2 exposure is associated with health risk and mortality caused by respiratory tract diseases, lung cancer, and cardiovascular diseases (Meltzer et al, 2009;Kan et al, 2010;Meng et al, 2013;Guarnieri and Balmes, 2014). The greatest RRs in mortality number with a 10 mg/m 3 increase of SO 2 were CO is a colorless, tasteless, odorless, and nonirritating gas that is a product of incomplete combustion of carbon-containing fuels (Nathan, 2007;Chen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Annual NO 2 concentration was higher in western Shenzhen, which can be related to greater traffic or indoor combustion emissions there. SO 2 is a traditional pollutant of industrial origin related to combustion of coal and other fossil fuels (Kan et al, 2010). SO 2 had greater concentrations in eastern Shenzhen, and the lowest CO concentrations were in the Luohu District.…”
Section: Discussionmentioning
confidence: 99%